Construction of coset codes in order to realize interference alignment - Watanabe, Cibele Cristina Trinca (2017)
Interference is usually viewed as an obstacle to communication in wireless networks. Therefore, we develop a new methodology to quantize the channel coefficients in order to realize interference alignment onto a 2-dimensional real lattice. In this work, we provide a method of channel quantization which is related to the real dimension 2 and, for that, we make use of the maximal real subfield of Q(ξ8), where ξ8 is the 8-th root of unity.